2006
DOI: 10.1186/1471-2296-7-44
|View full text |Cite
|
Sign up to set email alerts
|

Improving preventive service delivery at adult complete health check-ups: the Preventive health Evidence-based Recommendation Form (PERFORM) cluster randomized controlled trial

Abstract: Background: To determine the effectiveness of a single checklist reminder form to improve the delivery of preventive health services at adult health check-ups in a family practice setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 59 publications
2
46
2
Order By: Relevance
“…21 Paper or electronic evidencebased checklists have been designed to increase preventive care among adults of average risk. 22,23 Only 1 other clinical decision support system was found that addressed both prevention and therapeutic goals across diagnoses, using structured questions for patients and physicians to elicit more information related to the patient's chief complaint and linking the results to an electronic knowledge base. 24 However, its functionality was limited and it demonstrated no consistent pattern of clinician performance improvement.…”
Section: Discussionmentioning
confidence: 99%
“…21 Paper or electronic evidencebased checklists have been designed to increase preventive care among adults of average risk. 22,23 Only 1 other clinical decision support system was found that addressed both prevention and therapeutic goals across diagnoses, using structured questions for patients and physicians to elicit more information related to the patient's chief complaint and linking the results to an electronic knowledge base. 24 However, its functionality was limited and it demonstrated no consistent pattern of clinician performance improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Provider 5As performance Dubey et al looked at the effect of a one-page checklist reminder which prompted practitioners to provide evidence-based recommendations for preventive interventions. The study found a significant increase in the rate of cessation assistance being documented in patient charts (Dubey et al, 2006).…”
Section: Smoking Abstinencementioning
confidence: 97%
“…Several studies have examined ways to improve health promotion among adults in primary care (Dubey et al, 2006;Robinson et al, 2001). Recommendations include physician education seminars (Kersey et al, 1999), preventive health check lists (Miller et al, 2000;Moore & Siu, 1996), computer reminders (Dexter et al, 2001), use of non-physician staff to screen for disease (Moore et al, 1997), addressing preventive health topics at multiple visits (Reuben et al, 2003), and maintaining a periodic health examination (Sox et al, 1997).…”
Section: Conclusion and Discussionmentioning
confidence: 99%